HUBUNGAN GAYA KEPEMIMPINAN DAN MOTIVASI KERJA DENGAN DISIPLIN KERJA PEGAWAI KANTOR PERTANAHAN KOTA SEMARANG - Anisa Kusuma; Herbasuki Nurcahyanto; Aufarul Marom (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2015)
A clerk as human resources main in running an organization prosecuted not only have the skills and the ability of course but also is required to adhere to and obey regulation that has been set previously organization , hence needed real role of a leader to invite and affect employees to obey existing regulation by applying force leadership that effective .A style of leadership that effectively will not give influential if there is no support spirit and desire in self employees as motivation in self employees to comply with rules and norms existing in order to create prime services for the community and the goals of the organization. This research both type research ( explanation ) who tried to explain the relationship between variables as well as test a hypothesis that has been formulated , where researchers trying to find out the relationship between the style of leadership and motivation working with the awareness of discipline the land office semarang city , with the total sample 34 people employees .Data collection by observation , the questionnaire , interviews and a literature review , then analyzed in qualitative and quantitative ways .The testing of hypotheses with using analysis koefisiensi correlation rank kendall , konkordasi kendall and to know the size of the relationship between variables used koefisiensi analysis determined with the help of spss program. The research results show that the relationship with the leadership style discipline to 15.5 %, while relations with the motivation of the work of work discipline 21,9 % and discipline of work associated with the style of leadership and motivation simultaneously by 6 percent .The results of research shows that there is a positive relationship between the style of leadership and motivation of employees to work discipline employees work .Recommendations that the author of give it that is underscored the rules and good governance and working in imposing real doubtful , the need of adjustment of the style of leadership that applied by the leader with the level of maturity employees , and the last need the support of leaders such as the appreciation and praise directly as a form of appreciation to the employees.